DRAMATURGI: BUDAYA FLEXING BERKEDOK PENIPUAN DI MEDIA SOSIAL (STUDI KASUS INDRA KENZ DAN DONI SALMANAN) - nurma yuwita; Naili Mauhibatillah; Himmatul ‘Ulyah (Prodi Ilmu Komunikasi Universitas Putera Batam, 2022)
Flexing is a term used for someone who often shows off his wealth. Flexing culture is now becoming a sensational phenomenon in society since the arrests of Indra Kenz and Doni Salmanan. As binary option affiliates, Indra Kenz and Doni Salmanan often show off their wealth in their social media accounts so that they are known as Crazy Rich Medan and Crazy Rich Bandung. But behind that, they also try to cover up the cover of their fraud so that it is not known by others. This study aims to analyze the cases of Indra Kenz and Doni Salmanan as binary option affiliators. This research approach uses a qualitative descriptive approach. The researcher uses the theory of dramaturgy by Erving Goffman, which will analyze the front stage and back stage performed by Indra Kenz and Doni Salmanan. From the results of the analysis it can be seen that Indra Kenz and Doni Salmanan flexed on social media with the aim of attracting victims to participate in binary options trading so that they can reap huge profits from the victims' losses, but behind that they are also trying to cover up the guise of their fraud. As binary option affiliates, they try to present everything that is good about themselves (front stage) and cover their cover (back stage).